2010
DOI: 10.1002/anie.201003110
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced Water Splitting with Hematite: Improved Nanostructure and Iridium Oxide Catalysis

Abstract: Revved‐up rust! Light‐induced water splitting over iron oxide (hematite) has been achieved by using a particle‐assisted deposition technique and IrO2‐based surface catalysis. Photocurrents in excess of 3 mA cm−2 were obtained at +1.23 V versus the reversible hydrogen electrode under AM 1.5 G 100 mW cm−2 simulated sunlight. These photocurrents are unmatched by any other oxide‐based photoanode. FTO=fluorine‐doped tin oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
693
7
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,014 publications
(733 citation statements)
references
References 29 publications
30
693
7
3
Order By: Relevance
“…Tilley et al used a layer of IrO 2 nanoparticles ($2 nm diameter) on hematite photoanodes by electrodeposition, resulting in a cathodic shi in the onset potential from 1.0 V to 0.8 V vs. RHE. 59 Riha et al reported that cobalt oxide monolayers and partial monolayers were successfully coated on hematite photoanodes by an atomic layer deposition method. 41 A stable 100 mV cathodic shi in onset potential was achieved on the planar device, and an even higher cathodic shi of $200 mV was obtained on an inverse opal hematite scaffold.…”
mentioning
confidence: 99%
“…Tilley et al used a layer of IrO 2 nanoparticles ($2 nm diameter) on hematite photoanodes by electrodeposition, resulting in a cathodic shi in the onset potential from 1.0 V to 0.8 V vs. RHE. 59 Riha et al reported that cobalt oxide monolayers and partial monolayers were successfully coated on hematite photoanodes by an atomic layer deposition method. 41 A stable 100 mV cathodic shi in onset potential was achieved on the planar device, and an even higher cathodic shi of $200 mV was obtained on an inverse opal hematite scaffold.…”
mentioning
confidence: 99%
“…14,15 Si 4+ has been shown to be an effective n-type dopant in hematite photoanodes for water oxidation. [16][17][18] Despite this, the electronic properties of silicon-doped single crystal hematite have not been reported. Recently, Zhao et al 12 synthesized…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Intense current research efforts have been aimed at optimizing PEC performance by controlling the hematite structure, morphology, and surface chemistry and understanding fundamental charge carrier dynamics. 2,3,7,9,10 Despite these efforts, little is known about the spectral signatures and dynamics of photogenerated electrons and holes in these electrodes under water oxidation conditions.…”
mentioning
confidence: 99%